If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 2y + -3 = 0 Reorder the terms: -3 + 5x + 2y = 0 Solving -3 + 5x + 2y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 5x + 3 + 2y = 0 + 3 Reorder the terms: -3 + 3 + 5x + 2y = 0 + 3 Combine like terms: -3 + 3 = 0 0 + 5x + 2y = 0 + 3 5x + 2y = 0 + 3 Combine like terms: 0 + 3 = 3 5x + 2y = 3 Add '-2y' to each side of the equation. 5x + 2y + -2y = 3 + -2y Combine like terms: 2y + -2y = 0 5x + 0 = 3 + -2y 5x = 3 + -2y Divide each side by '5'. x = 0.6 + -0.4y Simplifying x = 0.6 + -0.4y
| 6n-3n+2n=20 | | -30+5y=15 | | 5c+2=2c+17 | | 6(x+2)=2(2x-4) | | 0.9-x=1.9 | | 4y-3y=11 | | 6b-3+2b=13 | | 4y=8x-20 | | 9x(8x+10)=180 | | 9y=10x-25 | | (92/23)^3=240/V | | 5y=7x-16 | | 5c^2+8c-4=0 | | 19b-17b=12 | | 5x+24=3x+8 | | 16,5+x/2=20 | | 2a/3=6 | | 2x*-4=-1/2*x+6 | | 8[50s]= | | 18u+-10u+-2y=18 | | 3c^2+3=-10c | | -3500+60x=0-90x | | 0-90x=-3500 | | 2g+4g-2g-g=18 | | 9[70s]= | | 2X-4=-0.5X+6 | | 16+17*3+x=20 | | 13h-12h+4h+2h+3h=10 | | 9[7s]= | | 1/3a=6 | | 16+17+x*3=20 | | 7(x-19)=7*3 |